(3GdSMH GdhGHdI Ydi VQGFM GdMfGHdIs - (3GHf MejOj , eMeO Hf YHO Gddg Hf Ydj Hf YKeGf Hf MejO GdYGeQj,J (B1295 (3g` s ((3eMeO Hf GSeGYjd Gdejefi GdeYQha HGdTfGhi s)
(3ChdgG (B:s
(3CMeO ef QaY ebOGQ GdYdeGA hLYdge CYdGekG s
(3HBNQgG JQLeI ddeDda hHChdgG agQSJ JaUjdi HCSeGA GdeJQLejfs
(3cJHgG HQSe GdTjN CHj HcQ Hf eMeO Hf eMeO YGQa NhbjQ Gdeci GdMfHdi GdcJHjs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B243 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B227s
Keywords: (3GdJGQjNs